Impact of socioeconomic characteristics of local community on forests outside protected areas of Sudan - Bello, Abdel Raouf Suleiman (Advances in Social Sciences Research Journal, 2016)
This study investigates the relationship between some respondent’s socioeconomic characteristics and forests’ uses in the Nuba Mountains region of Sudan. A total of 100 respondents were randomly selected from 4 localities. Data were obtained through interview schedule and observation. Frequency distribution, means and standard deviation, independent T-test, correlation and analysis of variance (ANOVA) methods were used for data analysis. On a 5 point scale, the study results revealed that 64% of respondents were highly dependent on forest to obtained fuel wood with mean 3.3 and SD 1.0702. There is a negative correlation statistically significant between respondent’s income and forest’s uses for building materials, grazing, hunting, and charcoal and beekeeping. No significant correlation between income level and forest’s uses for fuel wood, furniture and entertainment. The findings also revealed significant and negative relationship between some forests’ uses not significantly correlated to forest’s distance. Independent T-Test results revealed statistically significant differences, and/or non-significance between male and female in for forests’ such as fuel wood, building materials, furniture and others. Results also identified statistically significant and/or not significant differences between rural and urban residence in forests uses for some variables. One-way analysis of variance identified factors that are significantly and/or not significantly affect forests’ uses regarding respondents’ occupations. The study recommended introduction of relevant forestry management systems, extension activities on development and forest protection, adoption and dissemination of alternative energy sources such as cooking gas and others.